Improving the Quality of Islamic Religious Education Through Integration Madrasah Diniyah in Formal Schools - Muh. Syafiun Nuroyn; Muhammad Fatchur Rochim; Imam Syafi'i (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research comprehensively discusses the integration of Madrasah Diniyah in an effort to improve the quality of Islamic Religious Education (PAI) at Khazanah Ilmu Elementary School, Sidoarjo. The primary focus of this study is the implementation of Madrasah Diniyah within the school environment and its role in strengthening the quality of Islamic Religious Education. The research approach used was a qualitative descriptive case study. The researchers conducted field research at Khazanah Ilmu Elementary School, Sidoarjo, using various data collection techniques, such as observation, interviews, and documentation. Data sources consisted of primary data obtained directly from the research subjects and secondary data derived from documents and supporting literature. The collected data were then analyzed through the stages of data condensation, data presentation, and systematic conclusion drawing. The results indicate that Madrasah Diniyah at Khazanah Ilmu Elementary School, Sidoarjo, falls into the category of Complementary Madrasah Diniyah, namely a religious educational institution that functions as a companion, complement, and reinforcement to formal education at the elementary school. The role of Madrasah Diniyah in improving the quality of Islamic Religious Education encompasses two main aspects. First, the Madrasah Diniyah serves as a reinforcement of the Islamic Religious Education (PAI) curriculum, with a more in-depth and specific presentation of material, covering the areas of the Qur'an and Hadith, Aqidah and Akhlak (Islamic Creed), Jurisprudence (Fiqh), Islamic Cultural History (SKI), and Arabic. Second, this institution functions as a means of fostering students' morals through intensive religious habituation activities, such as congregational prayer, PHBI (Islamic Religious Life), and other Islamic activities. Thus, the integration of the Madrasah Diniyah at Khazanah Ilmu Elementary School in Sidoarjo not only enriches the academic and religious aspects but also shapes the character and morality of students holistically.